Achievement of graduates on skills that have been given by Education University - Hariyanto, Agus; Nudin, Salamun Rohman; Nurul, Siti Hidayati; Rahman, Yunanfathur; Kautsar, Achmad (Technium Social Sciences Journal, 2021)
An important aspect of quality in higher education is the quality of achieved results. Higher education adds value by developing work-related skills and competencies to prepare students for the workplace. Tracer study is an effective medium used to track the absorption of alumni of a university in the world of work. This descriptive study involved graduates of Universitas Negeri Surabaya who completed their formal education in 2018. Contact details of graduates were sought and obtained from various sources, including notes from alumni. The results show that there is a need for an evaluation by Universitas Negeri Surabaya in terms of producing entrepreneurial graduates that need to be improved. Furthermore, this result also shifts the paradigm that education-based universities will produce graduates with the majority of teachers, but in fact most alumni work in private companies at the national level. It is hoped that in the future the university will be able to create programs that encourage prospective graduates to compete for jobs in companies or institutions on a national scale, by forming an international-based curriculum and registering superior departments to be internationally accredited.